Women leadership from Islamic perspective - Hassan, Zaharah; Abdul Aziz, Siti Fardaniah; Silong, Abu Daud (2011)
The small number of women at decision-making level is a universal phenomenon but it is more significant in many Islamic countries. This raises the issue whether Islam seems to be the obstacle for women advancement in leadership position. Ironically, there are differences in opinions regarding this matter. Many scholars think that the reason for this is due to cultural and social constraints regarding women’s roles in society. Another reason is the continuous stereotyping over the role of women being the assistance or to complement the opposite sex. Hence, this paper attempts to explore opinions regarding the position of women as leaders in Islam. Specifically, it will focus on the roles, achievement and challenges encountered by the women leaders in Malaysia. Recommendations are put forward in order to overcome this issue.